Testing Sweet Pepper Variety Samples in Spring Greenhouses - Nurkabilovich, Mamayusupov Abbos (Journal of Geography, Regional Planning and Development, 2024)
In-depth scientific analysis of the results of the research carried out for the purpose of testing sweet pepper variety samples in spring greenhouses is presented.